2018
DOI: 10.1515/ats-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of the health implications of use of biomass energy sources among women in rural households of Jigawa State, Nigeria

Abstract: Various health challenges and fatalities in rural communities of most developing countries of the world have been traceable to the unabated use of biomass energy sources. We therefore assessed the awareness of the health implications of the use of biomass energy sources among women in rural households of Jigawa State. Multistage sampling procedure was used to collect data from 120 respondents using structured questionnaires. Data were collected on respondents’ socioeconomic characteristics, types of biomass us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…The level of dependence on fuel wood is high. The result from this study agreed with Orifah et al (2018), who reported that rural people in Dutse depend largely on wood and charcoal as a dominant biomass energy sources. The respondents were of the opinion that wind damage can be curtailed through tree planting exercise even though their participation in reforesting the environment was insignificant.…”
Section: Discussionsupporting
confidence: 92%
“…The level of dependence on fuel wood is high. The result from this study agreed with Orifah et al (2018), who reported that rural people in Dutse depend largely on wood and charcoal as a dominant biomass energy sources. The respondents were of the opinion that wind damage can be curtailed through tree planting exercise even though their participation in reforesting the environment was insignificant.…”
Section: Discussionsupporting
confidence: 92%
“…The link between energy poverty and economic development on both the micro and macro levels have been examined in several studies (Mchakulu et Orifah et al, 2018). The continual use of BSF has immensely led to energy poverty in most SSA households.…”
Section: The Impacts Of the Use Of Biomass Solid Fuel In Cookingmentioning
confidence: 99%
“…It should be noted that there is considerably high level of awareness of the health implications from the use of wood fuels among SSA women [102][103]. Despite this, these fuels have continued to be in use due to high cost of the alternatives, scarcity of refilling points for alternatives (especially in rural areas) and lack of capital [103]. Given these hindrances, it is likely that domestic use of wood fuels will become even more widespread in this population [12].…”
Section: Recommendationsmentioning
confidence: 99%